1981
DOI: 10.1128/aac.19.2.260
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal binding region for the antibiotic tiamulin: stoichiometry, subunit location, and affinity for various analogs

Abstract: Equilibrium dialysis experiments with a highly purified preparation of labeled tiamulin, a semisynthetic derivative of the antibiotic pleuromutilin, and Escherichia coli ribosomes allowed the determination of two binding sites for the drug. The binding reaction showed a cooperative effect. Of the two subunits, the 50S particle was able to bind the antibiotic in a 1:1 stoichiometry. Hence, the 50S subunit contributed predominantly to the binding energy which held the antibiotic to the ribosomes. The 30S subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Either the system “pays” that cost and then benefits from stacking interactions with U2504 (2539), which is what happens when linezolid binds (Figure 4e), or it does not, which is the outcome when tiamulin binds (Figure 4a). In either case, both linezolid and tiamulin should bind more strongly to eubacterial ribosomes than they do to eukaryotic/archaeal ribosomes, 36,37 and hence preferentially inhibit the former. [Preliminary data obtained in the course of this work indicate that the MIC for H. ma for tiamulin is ~ 400 μg/ml (~0.66 mM), which is about 8 times its MIC for E. coli and 8000 times its MIC for S. aureus 7(Gurel, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Either the system “pays” that cost and then benefits from stacking interactions with U2504 (2539), which is what happens when linezolid binds (Figure 4e), or it does not, which is the outcome when tiamulin binds (Figure 4a). In either case, both linezolid and tiamulin should bind more strongly to eubacterial ribosomes than they do to eukaryotic/archaeal ribosomes, 36,37 and hence preferentially inhibit the former. [Preliminary data obtained in the course of this work indicate that the MIC for H. ma for tiamulin is ~ 400 μg/ml (~0.66 mM), which is about 8 times its MIC for E. coli and 8000 times its MIC for S. aureus 7(Gurel, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Paromomycin II A-site 1j7t, 203w [206] 82 Pleuromutilin PTC 80% protection at 20 µM 2ogo,ogn,ogo [207] 83 Pristinamycin IIA PTC 0.14 µM [208] 84 Promazine HIV-1 TAR Not reported [209] 84 Protoporphyrin IX tRNA/M1 RNA 3.5 µM [210] 85 Puromycin 50S A-site 480 µM 1q82 [211][212][213] 86 Quenosine Riboswitch 20 nM [214] 87 Quinacridone HIV-1 TAR~1 µM [215] 88 Quinupristin PTC 0.32/2.5 µM 1sm1 [175] 89 Ralenova (mitoxantrone) HIV-1 psi RNA/hvg RNA~10 µM (hvg RNA) [216] 90 Rbt203 HIV-1 TAR RNA 2 µM 1uud [217] [191] 98 S-adenosyl methionine Riboswitch <100 nM 2gis [220] 99 Sisomicin HCV IRES IIId 260nM [221] 100 Spectinomycin Small subunit 260 nM 1fjg [222] 101 Spiramycin A Exit tunnel, 50S 1.8 µM from kinetic data 1kd1 [163,223] …”
Section: Number Ligand Targetmentioning
confidence: 96%
“…Studies utilizing tiamulin, valnemulin and others chemically related substances demonstrated that pleuromutilins act as bacterial protein biosynthesis inhibitors [29][30][31][32][33]. These substances bind to 70S ribosome which is composed of two subunits, a small (30S) and a large (50S) [34,35].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…It is important to mention that the binding site of pleuromutilins is different from erythromycin ( Fig. 5) compete with pleuromutilins for binding to the ribosome [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. However, other antibiotics such as chloramphenicol (Fig.…”
Section: Mechanism Of Actionmentioning
confidence: 99%